Hepatitis B virus infection in pregnant women in Baghdad - Ismail , Hujaz (AL-Kindy College Medical Journal, 2013)
Background: Globally, hepatitis B is one of the most common infectious diseases. Estimates indicate that at least 2 billion people have been infected with the hepatitis B virus (HBV), with more than 378 million people being chronic carriers. Those individuals at higher risk for acquiring HBV and transmitting disease like pregnant women should be screened for  hepatitis B surface  antigen (HBsAg) to prevent transmission by vaccination and operation.  Aim of study: The aim of this study was to determine the prevalence of HBsAg and its associated parameters in pregnant women who referred to antenatal clinic in Baghdad Province. Methods: The 234 apparently healthy pregnant women and their families, husbands and children were selected as study subjects from among those who had attained prenatal care clinic in Baghdad province between 2010  to 2012. Serological test was done for HBV using ELISA test (Dialab REF:Z00360,LOT2052-2). Results: Of these, 234 cases were brought into the study. Their age were ranged from 16-42 years old. Based on a different parameters , women positive for HBV and their children were negative constitute the highest percentage 85.4% and lowest one was pregnant women who lived with positive family history of HBV were 8.9%.  Conclusions: The seroprevalence of HBsAg was of moderate severity according to WHO. This finding would suggest for the introduction of routine screening for HBV to all pregnant women during the antenatal period, and that “at birth dose” vaccination is given to new born babies of mothers found to be HBsAg positive so as to reduce and prevent the spread of infection. However more data is required from larger studies to support the findings so that ultimately this can be recommended as a policy. Background: Globally, hepatitis B is one of the most common infectious diseases. Estimates indicate that at least 2 billion people have been infected with the hepatitis B virus (HBV), with more than 378 million people being chronic carriers. Those individuals at higher risk for acquiring HBV and transmitting disease like pregnant women should be screened for  hepatitis B surface  antigen (HBsAg) to prevent transmission by vaccination and operation.  Aim of study: The aim of this study was to determine the prevalence of HBsAg and its associated parameters in pregnant women who referred to antenatal clinic in Baghdad Province. Methods: The 234 apparently healthy pregnant women and their families, husbands and children were selected as study subjects from among those who had attained prenatal care clinic in Baghdad province between 2010  to 2012. Serological test was done for HBV using ELISA test (Dialab REF:Z00360,LOT2052-2). Results: Of these, 234 cases were brought into the study. Their age were ranged from 16-42 years old. Based on a different parameters , women positive for HBV and their children were negative constitute the highest percentage 85.4% and lowest one was pregnant women who lived with positive family history of HBV were 8.9%.  Conclusions: The seroprevalence of HBsAg was of moderate severity according to WHO. This finding would suggest for the introduction of routine screening for HBV to all pregnant women during the antenatal period, and that “at birth dose” vaccination is given to new born babies of mothers found to be HBsAg positive so as to reduce and prevent the spread of infection. However more data is required from larger studies to support the findings so that ultimately this can be recommended as a policy. Background: Globally, hepatitis B is one of the most common infectious diseases. Estimates indicate that at least 2 billion people have been infected with the hepatitis B virus (HBV), with more than 378 million people being chronic carriers. Those individuals at higher risk for acquiring HBV and transmitting disease like pregnant women should be screened for  hepatitis B surface  antigen (HBsAg) to prevent transmission by vaccination and operation.  Aim of study: The aim of this study was to determine the prevalence of HBsAg and its associated parameters in pregnant women who referred to antenatal clinic in Baghdad Province. Methods: The 234 apparently healthy pregnant women and their families, husbands and children were selected as study subjects from among those who had attained prenatal care clinic in Baghdad province between 2010  to 2012. Serological test was done for HBV using ELISA test (Dialab REF:Z00360,LOT2052-2). Results: Of these, 234 cases were brought into the study. Their age were ranged from 16-42 years old. Based on a different parameters , women positive for HBV and their children were negative constitute the highest percentage 85.4% and lowest one was pregnant women who lived with positive family history of HBV were 8.9%.  Conclusions: The seroprevalence of HBsAg was of moderate severity according to WHO. This finding would suggest for the introduction of routine screening for HBV to all pregnant women during the antenatal period, and that “at birth dose” vaccination is given to new born babies of mothers found to be HBsAg positive so as to reduce and prevent the spread of infection. However more data is required from larger studies to support the findings so that ultimately this can be recommended as a policy. Background: Globally, hepatitis B is one of the most common infectious diseases. Estimates indicate that at least 2 billion people have been infected with the hepatitis B virus (HBV), with more than 378 million people being chronic carriers. Those individuals at higher risk for acquiring HBV and transmitting disease like pregnant women should be screened for  hepatitis B surface  antigen (HBsAg) to prevent transmission by vaccination and operation.  Aim of study: The aim of this study was to determine the prevalence of HBsAg and its associated parameters in pregnant women who referred to antenatal clinic in Baghdad Province. Methods: The 234 apparently healthy pregnant women and their families, husbands and children were selected as study subjects from among those who had attained prenatal care clinic in Baghdad province between 2010  to 2012. Serological test was done for HBV using ELISA test (Dialab REF:Z00360,LOT2052-2). Results: Of these, 234 cases were brought into the study. Their age were ranged from 16-42 years old. Based on a different parameters , women positive for HBV and their children were negative constitute the highest percentage 85.4% and lowest one was pregnant women who lived with positive family history of HBV were 8.9%.  Conclusions: The seroprevalence of HBsAg was of moderate severity according to WHO. This finding would suggest for the introduction of routine screening for HBV to all pregnant women during the antenatal period, and that “at birth dose” vaccination is given to new born babies of mothers found to be HBsAg positive so as to reduce and prevent the spread of infection. However more data is required from larger studies to support the findings so that ultimately this can be recommended as a policy.